Use of multifunctional phosphorylated PAMAM dendrimers for dentin biomimetic remineralization and dentinal tubule occlusion. Issue 15 (25th February 2015) - Wang, Tianda; Yang, Sheng; Wang, Lei; Feng, Hailan
<x xml:space="preserve">Abstract</x> Phosphorylated poly(amidoamine) dendrimers can induce biomimetic remineralization of demineralized dentin as analogs of non-collagenous proteins in the presence of polyacrylic acid, an amorphous calcium phosphate stabilizing agent.